Prognostic value of 2-[18F]FDG PET-CT in metastatic melanoma patients receiving immunotherapy. Issue 146 (January 2022) - Schweighofer-Zwink, Gregor; Manafi-Farid, Reyhaneh; Kölblinger, Peter; Hehenwarter, Lukas; Harsini, Sara; Pirich, Christian; Beheshti, Mohsen
Highlights: [ 18 F]FDG PET/CT can be used to predict patients' outcomes, receiving immunotherapy. Metabolic parameters are strong predictors of overall survival. Follow-up PET after 3 months of immunotherapy provided stronger predictive parameters. Tumor-to-background ratios were more powerful compared to MTV and TLG. Abstract: Purpose: The 2-fluorodeoxyglucose positron emission tomography/computed tomography (2-[ 18 F]FDG PET/CT) is used for the evaluation of response to immunotherapy in malignant melanoma. Here, we evaluated the prognostic value of various metabolic parameters in baseline and different time points after therapy. Methods: In this retrospective study, 51 metastatic melanoma patients, who had received immunotherapy, were included. Patients with baseline and two follow-up 2-[ 18 F]FDG PET/CT studies (3 and 6 months after therapy) were selected. Multiple metabolic parameters and tumor-to-background ratios (TBRs) were extracted and correlated with OS. Results: The 3- and 5-year OS rates were 49% and 43.1%, respectively. On baseline 2-[ 18 F]FDG PET/CT, only standardized uptake value corrected for lean body mass (SULmax and SULpeak ), as well as most of the TBRs were predictive for 3- and 5-year OS rates. Metabolic tumor volume (MTV), total lesion glycolysis (TLG), and most of the TBRs were predictive on both follow-up studies. Also, the changes in values of MTV, TLG and most of the TBRs from the baseline to the 3-month and 6- month follow-up studies were prognostic. On multivariate analysis, all of the most predictive parameters for OS were derived from the 3-month follow-up study. The ratio of TBRmean to the mediastinum was the best factor (cutoff value of 2.15, sensitivity of 88.5% and specificity of 68.0% for 3-year survival). Conclusion: Metabolic parameters derived from 2-[ 18 F]FDG PET/CT are valuable tools for the prediction of 3- and 5-year OS rates in metastatic melanoma patients undergoing immunotherapy. The 3-month follow-up 2-[ 18 F]FDG PET/CT is of particular importance in this regard.